Espaço aéreo durante a tensão e conflito entre Rússia e Ucrânia - Thiago Oliveira Neto (Confins)
The recent conflict directly involving Ukraine and Russia, as of February 2022, had several spatial impacts constituted by the advances of troops in the territory, migratory flows and the several displacements of aircraft in the airspace. The latter can be observed remotely when aircraft have technical equipment that makes the aircraft visible in real time and with the information available through apps and websites over the internet. Based on this free access tool, it was selected some images of Ukrainian, Russian and European airspace that appear several military aircraft and drones.